A consistent data model for different data granularity in control charts. Issue Volume 34:Issues 2(2022) (3rd April 2022) - Grimshaw, Scott D.
Abstract: After a long-running show was canceled, control charts are used to identify if and when viewing drops. The finest granularity daily viewing has high autocorrelation and control charts use residuals from a seasonal ARIMA model. For coarse granularity data (weekly and monthly viewing) an approximate AR model is derived to be consistent with the finest granularity model. With the proposed approach, a longer memory model is used in the granular data control charts that reduces the number of false alarms from control charts constructed treating granular data as a different measurement.